Penerapan Model Pembelajaran Andragogical Content Knowledge (ACK) pada Mata Kuliah Psikologi Sosial - Fatmawati Gaffar Muhammad Gaffar; Muhammad Hasan, SKM, M.Kes; Dr. Hj. Kartini Marzuki, M.Si (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2020)
The author’s observations during conducting research in the lecture process, especially semester III students of the 2018 class of Social Psychology, Departemen of Educational Outside of School most of the students have different abilities, especially in interacting with lecturers in terms of expressing opinions and fellow participants when discussing or listening to lecture material so that from such conditions surely each student has a different level of unserstansing. From these data it is known that applying the learning model of Andrgogical Content Knowledge (ACK) is very important to support the contions of student learning in class to be optimal so that it can lead to optimal learning outcomes as expected. This study aims to find out and study about the Application of The Learning Model of Andragogical Content Knowledge (ACK) in Social Psychology Subject (Studies in the Department of Outside Education, Makassar State University). Data collection is done by using interviews, observation and documentation. The application of the Andragogical Content Knowledge (ACK) Learning Model in Social Psychology Subject (Studies in the School of Education Department of the Faculty of Education, Makassar State University) can improve students ability to engage in social interaction so that they can be directly involved actively participating as long as the program is implemented. This learning model, is very effective to be applied in learning and training activities especially for students and adults as trainees who need additional experience to increase learning independence.